New-look institute for Burundi - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
Burundi has recently overhauled its national agricultural research institute to improve productivity in order to be able to respond better to farmers' needs. The Burundi Institute of Agricultural Sciences (ISABU), has reorganized and expanded its...